Accelerated Investment as a Force in Economic Development: Comment - de Schweinitz, Karl (Quarterly Journal of Economics, 1959)
Journal Article Accelerated Investment as a Force in Economic Development: Comment Get access Karl de Schweinitz, Jr. Karl de Schweinitz, Jr. Northwestern University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 73, Issue 3, August 1959, Pages 499–502, https://doi.org/10.2307/1880618 Published: 01 August 1959